Hotel Development Guidelines for Elderly Tourists - Bootsaranon, Saovarat; Sudsomboon, Sudarat (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
Nowadays, we are dealing with change in age structures of world population which tends to continually increase. Many of the elderly spend their lives travelling for pleasure after retirement or staying in a hotel which can respond to their needs. Yet, most hotels lack suitable facilities for the elderly including ramps for stairs, ramps with handrails along hotel pathways, hotel rooms with an emergency assistance alarm, or other services such as healthy food restaurants, spa, health massage, and so forth. Thus, hotel entrepreneurs should be aware of all these needs in order to provide those elderly tourists with suitable services.